Answer:
Your solution is (-1, 0)
Explanation:
3x - y = -3
x + y = -1
The elimination method eliminates one variable at a time to find the other variable.
Here we can see that the y variable will naturally be eliminated.
3x - y = -3
x + y = -1
--------------
4x = -4
Divide both sides by 4 to isolate x.
x = -1
Now plug this value back into one of the equations.
3(-1) - y = -3
Multiply.
-3 - y = -3
Add 3 to both sides.
-y = 0
Divide both sides by -1.
y = 0
Your solution is (-1, 0)
Check this solution by plugging these values into the second equation.
-1 + 0 = -1
-1 = -1
Your solution is correct.
Hope this helps!